Framing The Gender Equality in IAIN Ponorogo Indonesia - Anis Hidayatul Imtihanah; Asep Syahrul Mubarok (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2021)
Women play many roles in today's world in their societies' economic development. Women have many contributions to a country's welfare in various sectors, such as politics, health, agriculture, and public education. This research used a mixed-method design to analyze Islamic higher education, focusing on implementing gender policy and gender values—moreover, the activities of female lecturers in their daily work. The research also combines qualitative and quantitative data-gathering methods, particularly participant observation, in-depth interviews, numbers data, and figures to analyze how gender equality values for women should be implemented. This research reveals that IAIN Ponorogo is responsive gender. It can be seen from women's involvement in multiple fields like the academic senate member and the journal manager. The research also argues that women should be given equal opportunities as men, including paid work and the decision-making position sectors, to contribute to the institution.